2022
DOI: 10.1097/bor.0000000000000894
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of caring for transgender and gender diverse patients with rheumatic disease: presentation of seven patients and review of the literature

Abstract: Purpose of reviewAs perspectives on sex and gender identity have evolved, there has been an increase in the practice of transgender medicine. Within rheumatology, however, there is a dearth of information about rheumatic disease in transgender and gender diverse (TGGD) individuals. This is important, as sex hormones affect the etiopathogenesis and expression of autoimmune diseases. We therefore sought to identify TGGD patients with rheumatic disease, review their clinical courses, and appraise existing literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Pakpoor et al [171] also reported elevated risk to developing multiple sclerosis in male-to-female transitioning. While the above indicate there is likely some risk in transitioning with hormonal treatment, there is also the issue of clinical care for those with rheumatic diseases who transition [172].…”
Section: Consequences Of Homosexuality and Gender Dysphoria On Health...mentioning
confidence: 99%
“…Pakpoor et al [171] also reported elevated risk to developing multiple sclerosis in male-to-female transitioning. While the above indicate there is likely some risk in transitioning with hormonal treatment, there is also the issue of clinical care for those with rheumatic diseases who transition [172].…”
Section: Consequences Of Homosexuality and Gender Dysphoria On Health...mentioning
confidence: 99%
“…The existence of a direct causation between the initiation of GAHT and the development or worsening of arthritis should be taken with caution due to the study’s limitations, mainly related to multiple confounders and probable publication bias. Higher-powered prospective studies are needed, and a registry would be valuable [ 80 ].…”
Section: Intersections Of Gendermentioning
confidence: 99%
“…27 A recent systematic literature review highlighted the lack of relevant clinical evidence and stressed the need for gender-diverse recruitment of participants in clinical trials to fill in the gaps in our knowledge. 28 Further research needs to be conducted to understand the experiences of such patients in rheumatology clinics.…”
Section: Disparities By Social Roles and Factorsmentioning
confidence: 99%